Lemur catta in small forest fragments: Which variables best predict population viability?. Issue 4 (30th January 2020) - Gould, Lisa; Cowen, Laura L. E.
Abstract: Habitat fragmentation is an increasingly serious issue affecting primates in most regions where they are found today. Populations of Lemur catta (ring‐tailed lemur) in Madagascar's south‐central region are increasingly restricted to small, isolated forest fragments, surrounded by grasslands or small‐scale agriculture. Our aim was to evaluate the potential for population viability of L. catta in nine forest fragments of varying sizes (2–46 ha, population range: 6–210 animals) in south‐central Madagascar, using a set of comparative, quantitative ecological measures. We used Poisson regression models with a log link function to examine the effects of fragment size, within‐fragment food availability, and abundance of matrix resources (food and water sources) on L. catta population sizes and juvenile recruitment. We found a strong association between overall population size and (a) fragment size and (b) abundance of key food resources Melia azedarach and Ficus spp. (per 100 m along transect lines). Juvenile recruitment was also associated with fragment size and abundance of the two above‐mentioned food resources. When the largest population, an outlier, was removed from the analysis, again, the model containing fragment size and abundance of M. azedarach and Ficus spp. was the best fitting, but the model that best predicted juvenile recruitment contained only fragment size. While our results are useful for predicting population presence and possible persistence in these fragments, both the potential for male dispersal and the extent of human disturbance within most fragments play crucial roles regarding the likelihood of long‐term L. catta survival. While seven of the nine fragments were reasonably protected from human disturbance, only three offered the strong potential for male dispersal, thus the long‐term viability of many of these populations is highly uncertain. Research Highlights: Fragment size and occurrence rate of key food trees are important predictors of population viability in Lemur catta confined to fragments in south‐central Madagascar. Lack of male dispersal opportunities and ongoing anthropogenic disturbance of some fragments compromises such viability. Abstract : Ring‐tailed lemur in the Anja Reserve forest fragment with adjacent rice field in the distance.